2022
DOI: 10.1002/wene.451
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID‐19 on the market prospects of electric passenger cars

Abstract: The outbreak of COVID‐19 pandemic has caused changes worldwide in a dimension that has not been seen since the Second World War. This pandemic and the measures taken to moderate the negative consequences have affected almost all aspects of our life. Transport has been one of the most affected sectors. In general, the global car market is very sensitive to macroeconomic conditions. This applies especially to electric vehicles, which are still very dependent on financial support measures. A combination of travel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…As Ajanovic indicated, car sales of the conventional ICE vehicles were about 17% lower than in 2019, but the sale of EVs was about 45% higher than in previous year. Furthermore, she pointed out that in Europe, electric car sales in 2020 increased by about 130% [11].…”
Section: The Growing Market Of Electric Vehiclesmentioning
confidence: 99%
See 2 more Smart Citations
“…As Ajanovic indicated, car sales of the conventional ICE vehicles were about 17% lower than in 2019, but the sale of EVs was about 45% higher than in previous year. Furthermore, she pointed out that in Europe, electric car sales in 2020 increased by about 130% [11].…”
Section: The Growing Market Of Electric Vehiclesmentioning
confidence: 99%
“…The increase in electric vehicle purchases could be explained for a variety of reasons during the time of COVID 19. As of pre COVID 19 situations, governments, like the aforementioned ones, are in favor of supporting the research of electric vehicles as a way to cut down on carbon and greenhouse emission, and all the funding the government provided contributed to lower battery cost over the years [11]. The lower battery cost meant it was lower to produce an electric vehicle, further meaning that it would be cheaper for consumers to be able to afford one.…”
Section: The Growing Market Of Electric Vehiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 3.2 million electric vehicles were registered worldwide in the first half of the year. The number of electric vehicle registrations in Europe has significantly increased, mostly as a result of stimulus plans launched by European governments and financial incentives such as tax reductions [3]. The surge in EV sales has consequently led to a notable increase in the production of lithium-ion batteries for EVs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies have found that people are shifting from using public transportations to private transportations in the US due to COVID [8], this might be similar in China in short term but in long run, people will gradually go back to their routine and use public transportations more. Previous study has found that electric cars was negatively impacted by COVID in short-term [9], but in this study COVID is not considered as an individual category, due to limited data.…”
Section: Literature Reviewmentioning
confidence: 99%